2022
DOI: 10.3390/ma15082896
|View full text |Cite
|
Sign up to set email alerts
|

A DFT/TD-DFT Study on the ESIPT-Type Flavonoid Derivatives with High Emission Intensity

Abstract: To reveal the influence of different substituents on the excited-state intramolecular proton transfer (ESIPT) process and photophysical properties of 4′-N, N-dimethylamino-3-hydroxyflavone (DMA3HF), two novel molecules (DMA3HF-CN and DMA3HF-NH2) were designed by introducing the classical electron-withdrawing group cyano (-CN) and electron-donating group amino (-NH2). The three molecules in the acetonitrile phase were systematically researched by applying the density functional theory (DFT) and time-dependent D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In previous work [32], we studied the influence of the confined environment on 3-hydroxyflavone (3HF) and 4 -N,N-diethylaminoflavonol (DEA3HF), which can proton-transfer in the excited state by the ESIPT (Excited State Intramolecular Proton Transfer) process. In this study, we observed that the dyes had a photophysical behavior close to that observed in an organic solvent solution; even encapsulated and solubilized in water, important properties were preserved, such as photochemical and photophysical stability and a large Stokes shift [33]. The solubility of organic dyes is often limited to organic solvents, and the use of the supramolecular approach, which involves confining a capsule with a water-soluble hydrophobic interior, using the OA capsule as the medium for this, significantly expands the study and applications of fluorescent compounds [34][35][36].…”
Section: Introductionmentioning
confidence: 66%
“…In previous work [32], we studied the influence of the confined environment on 3-hydroxyflavone (3HF) and 4 -N,N-diethylaminoflavonol (DEA3HF), which can proton-transfer in the excited state by the ESIPT (Excited State Intramolecular Proton Transfer) process. In this study, we observed that the dyes had a photophysical behavior close to that observed in an organic solvent solution; even encapsulated and solubilized in water, important properties were preserved, such as photochemical and photophysical stability and a large Stokes shift [33]. The solubility of organic dyes is often limited to organic solvents, and the use of the supramolecular approach, which involves confining a capsule with a water-soluble hydrophobic interior, using the OA capsule as the medium for this, significantly expands the study and applications of fluorescent compounds [34][35][36].…”
Section: Introductionmentioning
confidence: 66%
“…These result in bright fluorescence emission from KD-OH. 35,37 Application of KD-HNO in Living Cells. Based on the remarkable spectral performance of KD-HNO, we applied it to the biological sensing of HNO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, the KD-OH readily undergoes a rapid conversion from the enol form to the keto form in the excited state, forming a strong intramolecular hydrogen bond. These result in bright fluorescence emission from KD-OH . , …”
Section: Resultsmentioning
confidence: 99%
“…After the theoretical approach has been validated, the model can be further characterized through topological analysis. [56] This analysis is especially useful for the characterization of the hydrogen-bond strength, [57] because as a rule of thumb, a dye is more prone to suffer ESIPT if it presents a stronger intramolecular hydrogen bond. [58] The analysis of Non-Covalent Interactions (NCI) allows a further refinement of the description.…”
Section: Computer-assisted Decoding Esptmentioning
confidence: 99%